Added‐Value Surfactants. Issue 71 (30th October 2018) - Polarz, Sebastian; Kunkel, Marius; Donner, Adrian; Schlötter, Moritz
Abstract: Surfactants are ubiquitous in cellular membranes, detergents or as emulsification agents. Due to their amphiphilic properties, they cannot only mediate between two domains of very different solvent compatibility like water and organic but also show fascinating self‐assembly features resulting in micelles, vesicles, or lyotropic liquid crystals. The current review article highlights some approaches towards the next generation surfactants, for example, those with catalytically active heads. Furthermore, it is shown that amphiphilic properties can be obtained beyond the classical hydrophobic–hydrophilic interplay, for instance with surfactants containing one molecular block with a special shape. Whereas, classical surfactants are static, researchers have become more interested in species that are able to change their properties depending on external triggers. The article discusses examples for surfactants sensitive to chemical (e.g., pH value) or physical triggers (temperature, electric and magnetic fields). Abstract : More than soap : Surfactants with additional functionalities cross the current frontiers in self‐assembly research. The article highlights representative cases for catalytic surfactants and stimuli‐responsive amphiphiles.